Prioritizing smallholder animal health needs in East Africa, West Africa, and South Asia using three approaches: Literature review, expert workshops, and practitioner surveys - Campbell, Zoë A.; Coleman, P.; Guest, A.; Kushwaha, P.; Ramuthivheli, T.; Osebe, T.; Perry, Brian D.; Salt, Jeremy (Elsevier, 2021)
Managing the health needs of livestock contributes to reducing poverty and improving the livelihoods of smallholder and pastoralist livestock keepers globally. Animal health practitioners, producers, policymakers, and researchers all must prioritize how to mobilize limited resources. This study employed three approaches to prioritize animal health needs in East and West Africa and South Asia to identify diseases and syndromes that impact livestock keepers. The approaches were a) systematic literature review, b) a series of expert workshops, and c) a practitioner survey of veterinarians and para-veterinary professionals. The top constraints that emerged from all three approaches include endo/ ectoparasites, foot and mouth disease, brucellosis, peste des petits ruminants, Newcastle disease, and avian influenza. Expert workshops additionally identified contagious caprine pleuropneumonia, contagious bovine pleuropneumonia, mastitis, and reproductive disorders as constraints not emphasized in the literature review. Practitioner survey results additionally identified nutrition as a constraint for smallholder dairy and pastoralist small ruminant production. Experts attending the workshops agreed most constraints can be managed using existing veterinary technologies and best husbandry practices, which supports a shift away from focusing on individual diseases and new technologies towards addressing systemic challenges that limit access to veterinary services and inputs. Few research studies focused on incidence/ prevalence of disease and impact, suggesting better incorporation of socio-economic impact measures in future research would better represent the interests of livestock keepers.